Religion and Inequality in Africa - Chitando, Ezra (Bloomsbury Studies in Black Religion and Cultures Ser., 2023)
Intro -- Halftitle Page -- Title Page -- Contents -- List of contributors -- Introduction: Religion and inequality in Africa -- Part 1 Religion and inequality in Africa: Exploring the conundrum -- 1 Sleeping with the enemy: The entanglement of religions with inequalities in Nigeria -- 2 Religion and inequalities in Mozambique -- 3 Diaspora African communities, religion and inequality -- Part 2 Negotiating religion, gender and inequality in Africa -- 4 The one-man Jihad: Sarki Sanusi Lamido Sanusi (SLS) and Hausa Muslim women's status in Northern Nigeria -- 5 Negotiating gender inequality in religious fields: Bishop Margaret Wanjiru's use of charisma and social capital in Kenya -- 6 Interrogating the 'spiritual puzzle of silence' on religion and gender inequality in Tanzania -- 7 Religio-cultural beliefs and women's political participation: Gender dimensions in post-constitutional elections in Eswatini -- 8 Policing boundaries of the body? Spirit-type African Apostolic churches, HIV/AIDS and inequality in Eastern Zimbabwe, 1985-2015 -- 9 Religious homophobia and inequality in Malawi -- Part 3 Encountering religion, disability, age and inequality in Africa -- 10 Gender inequality and disability among the Ndebele religio-cultural communities: African women theologies of disabilities praxis -- 11 Born free? Born free for what? Exploring the lived experiences of Christian young adults in South Africa regarding inequality and social justice -- 12 Religion and income inequality among retirees in Botswana: A communal contextual theological approach -- Part 4 Religious movements and inequality -- 13 Dis/continuity of economic inequality and new prophetic churches in post-1994 South Africa -- 14 Prosperity, philanthropy and social differentiation: Neo-Pentecostalism and socioeconomic inequality in Harare.